Metal plasmas for the fabrication of nanostructures - André Anders (J. Phys. D: Appl. Phys., 2006)
A review is provided covering metal plasma production, the energetic condensation of metal plasmas, and the formation of nanostructures using such plasmas. Plasma production techniques include pulsed laser ablation, filtered cathodic arcs, and various forms of ionized physical vapor deposition, namely magnetron sputtering with ionization of sputtered atoms in radio frequency discharges, self-sputtering, and high power impulse magnetron sputtering. The discussion of energetic condensation focuses on the control of kinetic energy by biasing and also includes considerations of the potential energy and the processes occurring at subplantation and implantation. In the final section on nanostructures, two different approaches are discussed. In the top-down approach, the primary nanostructures are lithographically produced and metal plasma is used to coat or fill trenches and vias. Additionally, multilayers with nanosize periods (nanolaminates) can be produced. In the bottom-up approach, thermodynamic forces are used to fabricate nanocomposites and nanoporous materials by decomposition and dealloying.